2008
DOI: 10.1128/jb.00053-08
|View full text |Cite
|
Sign up to set email alerts
|

aro Mutations in Salmonella enterica Cause Defects in Cell Wall and Outer Membrane Integrity

Abstract: In this study we characterized aro mutants of Salmonella enterica serovars Enteritidis and Typhimurium, which are frequently used as live oral vaccines. We found that the aroA, aroD, and aroC mutants were sensitive to blood serum, albumen, EDTA, and ovotransferrin, and this defect could be complemented by an appropriate aro gene cloned in a plasmid. Subsequent microarray analysis of gene expression in the aroD mutant in serovar Typhimurium indicated that the reason for this sensitivity might be the upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…However, it is still unclear what difference between the ⌬aroA mutant and WT S. Typhimurium results in a weaker inflammatory response. Recently, it has been reported that the ⌬aroA mutant has defects in cell envelope biosynthesis, leading to weaker outer membrane integrity (45). Whether such structural differences between these mutants translate into differential expression of other innate immune ligands and/or interactions with host immune cells needs further investigation.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…However, it is still unclear what difference between the ⌬aroA mutant and WT S. Typhimurium results in a weaker inflammatory response. Recently, it has been reported that the ⌬aroA mutant has defects in cell envelope biosynthesis, leading to weaker outer membrane integrity (45). Whether such structural differences between these mutants translate into differential expression of other innate immune ligands and/or interactions with host immune cells needs further investigation.…”
Section: Vol 78 2010mentioning
confidence: 99%
“…-8 -To further explore the nature of the zebrafish Dar phenotype, a well-characterized attenuated mutant of S. Typhimurium (ΔaroA) was used [16]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli DH5α, Salmonella Typhimurium 14028 strain (wild type) and the ΔaroA mutant derivative [16] were grown in 20 mL of Luria-Bertani broth (Triptone 10g/L, Yeast extract, 5g/L, NaCl 5g/L) until stationary growth phase, under aerobic conditions, 37ºC and shaking at 180 rpm. The cells were harvested by centrifugation for 15 min at 6000 rpm at 25ºC.…”
Section: Bacterial Strains and Cell Conditionsmentioning
confidence: 99%
“…One strategy that has been used to obtain attenuated strains of microorganisms is to perform several mutations in the genes affecting bacterial metabolism, such as those associated with aromatic amino acids 6 . In this regard, the aro genes have become a mutational target for modification and virulence attenuation of pathogenic strains of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several mutations have been achieved in the aroA gene of Salmonella enterica, subsp. enterica serovar Abortus equi, and it was observed that one major effect produced by these mutations corresponds to the inability of the bacteria to generate aromatic metabolites, such as phenylalanine, tyrosine, and tryptophan, which are essential for bacterial metabolism; thus, these mutants are incapable of intracellular replication 6 . Additionally, these mutations altered the regulation of the murA gene, which is involved in peptidoglycan synthesis, thereby causing several defects in the bacterial cell wall and the outer bacterial membrane and facilitating phagocytosis of the mutant 6,8 .…”
Section: Introductionmentioning
confidence: 99%